Potential norms detection in social agent societies - Mahmoud M.A.; Mustapha A.; Ahmad M.S.; Ahmad A.; Yusoff M.Z.M.; Hamid N.H.A. (Springer Verlag, 2023)
In this paper, we propose a norms mining algorithm that detects a domain's potential norms, which we called the Potential Norms Mining Algorithm (PNMA). According to the literature, an agent changes or revises its norms based on variables of local environment and amount of thinking about its behaviour. Based on these variables, the PNMA is used to revise the norms and identify the new normative protocol to comply with the domain's norms. The objective of this research is to enable an agent to revise its norms without a third party enforcement unlike most of the work on norms detection and identification, which entail sanctions by an authority. We demonstrate the execution of the algorithm by testing it on a typical scenario and analyse the results on several issues. Springer International Publishing Switzerland 2013.